PEMBERANTASAN PENYAKIT DAN VAKSINASI HOG CHOLERA PADA TERNAK BABI DI DESA KELATING TABANAN - BERATA, BERATA; WINAYA, IB. OKA; SUARJANA, IGK.; SUARDANA, IB. KADE (Buletin Udayana Mengabdi; Vol 7 No 2 (2008): Volume 7 No.2 – September 2008, 2012)
ABSTRACT Swines are the most important livestock to Balinese people because raising the swines could analogized with save the money.. Beside that balines people considering swine livestock also have economically value for religious ceremonial. Field observation indicated that some disease can threating the swine, one of these is Hog cholera. Hog cholera is a highly contagious viral disease of swine that occur in acute, a subacute, a chronic or a persistent form. In Order to protect the Bali cattle against this disease need conducting regularly vaccination. By vaccination can improvement cattle immunity against this disease. The objective this services is reducing economic loss due to Hog cholera infection and also increased farmes an understanding to this disease. .